Overexpression of Artemisia annua Cinnamyl Alcohol Dehydrogenase Increases Lignin and Coumarin and Reduces Artemisinin and Other Sesquiterpenes - Ma, Dongming; Xu, Chong; Alejos-Gonzalez, Fatima; Wang, Hong; Yang, Jinfen; Judd, Rika; Xie, De-Yu (Frontiers in Plant Science, 2018)
Artemisia annua is the only medicinal crop that produces artemisinin for malarial treatment. Herein, we describe the cloning of a cinnamyl alcohol dehydrogenase (AaCAD) from an inbred self-pollinating (SP) A. annua cultivar and its effects on lignin and artemisinin production. A recombinant AaCAD was purified via heterogeneous expression. Enzyme assays showed that the recombinant AaCAD converted p-coumaryl, coniferyl, and sinapyl aldehydes to their corresponding alcohols, which are key intermediates involved in the biosynthesis of lignin. Km, Vmax, and Vmax/Km values were calculated for all three substrates. To characterize its function in planta, AaCAD was overexpressed in SP plants. Quantification using acetyl bromide (AcBr) showed significantly higher lignin contents in transgenics compared with wild-type (WT) plants. Moreover, GC-MS-based profiling revealed a significant increase in coumarin contents in transgenic plants. By contrast, HPLC-MS analysis showed significantly reduced artemisinin contents in transgenics compared with WT plants. Furthermore, GC-MS analysis revealed a decrease in the contents of arteannuin B and six other sesquiterpenes in transgenic plants. Confocal microscopy analysis showed the cytosolic localization of AaCAD. These data demonstrate that AaCAD plays a dual pathway function in the cytosol, in which it positively enhances lignin formation but negatively controls artemisinin formation. Based on these data, crosstalk between these two pathways mediated by AaCAD catalysis is discussed to understand the metabolic control of artemisinin biosynthesis in plants for high production.